Roles for Prlhr/GPR10 and Npffr2/GPR74 in feeding responses to PrRP - Yi Wang; Weiwei Qiu; Stace Kernodle; Carly Parker; Marc-Antonio Padilla; Jiaao Su; Abigail J. Tomlinson; Stephanie Oldham; Joss Field; Elise Bernard; David Hornigold; Christopher J. Rhodes; et al. (Molecular Metabolism)
Objective: Several groups of neurons in the NTS suppress food intake, including Prlh-expressing neurons (NTSPrlh cells). Not only does the artificial activation of NTSPrlh cells decrease feeding, but also the expression of Prlh (which encodes the neuropeptide PrRP) and neurotransmission by NTSPrlh neurons contributes to the restraint of food intake and body weight, especially in animals fed a high fat diet (HFD). We set out to determine roles for putative PrRP receptors in the response to NTS PrRP and exogenous PrRP-related peptides. Methods: We used animals lacking PrRP receptors GPR10 and/or GPR74 (encoded by Prlhr and Npffr2, respectively) to determine roles for each in the restraint of food intake and body weight by the increased expression of Prlh in NTSPrlh neurons (NTSPrlhOX mice) and in response to the anorectic PrRP analog, p52. Results: Although Prlhr played a crucial role in the restraint of food intake and body weight in HFD-fed control animals, the combined absence of Prlhr and Npffr2 was required to abrogate the restraint of food intake in NTSPrlhOX mice. p52 suppressed feeding independently of both receptors, however. Conclusions: Hence, each receptor can participate in the NTSPrlh-mediated suppression of food intake and body weight gain, while PrRP analog treatment can mediate its effects via distinct systems. While Prlhr plays a crucial role in the physiologic restraint of weight gain, the action of either receptor is capable of ameliorating obesity in response to enhanced NTSPrlh signaling.